Gastropareza na oddziale intensywnej terapii - Stojek, Magdalena; Jasiński, Tomasz (Anestezjologia Intensywna Terapia, 2021)
Gastroparesis is a common problem in the intensive care unit. Impaired gastric motility in critically ill patients is associated with an increased risk of enteral feeding intolerance, gastric bacterial colonization, pulmonary aspiration and progressive malnutrition leading to adverse outcomes. It is estimated that at least 60% of intensive care patients are affected by some form of gastrointestinal tract failure and that in 30% of critically ill patients in whom enteral feeding is attempted the feeding route needs to be modified because of feeding intolerance. The article highlights the physiology of normal gastric motor function and mechanisms of abnormal gastric motility as well as the current approach to detecting and treating feeding intolerance in intensive care.